Combined effects of cisplatin and photon or proton irradiation in cultured cells: radiosensitization, patterns of cell death and cell cycle distribution. (3rd September 2020) - Iwata, Hiromitsu; Shuto, Tsuyoshi; Kamei, Shunsuke; Omachi, Kohei; Moriuchi, Masataka; Omachi, Chihiro; Toshito, Toshiyuki; Hashimoto, Shingo; Nakajima, Koichiro; Sugie, Chikao; Ogino, Hiroyuki; Kai, Hirofumi; et al.
Abstract: The purpose of the current study was to investigate the biological effects of protons and photons in combination with cisplatin in cultured cells and elucidate the mechanisms responsible for their combined effects. To evaluate the sensitizing effects of cisplatin against X-rays and proton beams in HSG, EMT6 and V79 cells, the combination index, a simple measure for quantifying synergism, was estimated from cell survival curves using software capable of performing the Monte Carlo calculation. Cell death and apoptosis were assessed using live cell fluorescence imaging. HeLa and HSG cells expressing the fluorescent ubiquitination-based cell cycle indicator system (Fucci) were irradiated with X-rays and protons with cisplatin. Red and green fluorescence in the G1 and S/G2/M phases, respectively, were evaluated and changes in the cell cycle were assessed. The sensitizing effects of ≥1.5 μM cisplatin were observed for both X-ray and proton irradiation ( P  < 0.05). In the three cell lines, the average combination index was 0.82–1.00 for X-rays and 0.73–0.89 for protons, indicating stronger effects for protons. In time-lapse imaging, apoptosis markedly increased in the groups receiving ≥1.5 μM cisplatin + protons. The percentage of green S/G2/M phase cells at that time was higher when cisplatin was combined with proton beams than with X-rays ( P  < 0.05), suggesting more significant G2 arrest. Proton therapy plus ≥1.5 μM cisplatin is considered to be very effective. When combined with cisplatin, proton therapy appeared to induce greater apoptotic cell death and G2 arrest, which may partly account for the difference observed in the combined effects.